Strengthening Islamic Educational Identity through Islamic School Culture: Implementation of Daily Religious Practices in Madrasah Ibtidaiyah - Laili, Nifi; Ishari, Nurhafid; Ulumudin, Ihya’ (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Strengthening Islamic educational identity at the Madrasah Ibtidaiyah level is an important necessity amid the challenges of globalization that can affect the religious character of students. One strategy that is considered effective is through the implementation of Islamic school culture, which is manifested in daily religious practices. This study aims to analyze the strengthening of Islamic educational identity through Islamic school culture with an emphasis on the implementation of daily religious practices in Madrasah Ibtidaiyah. This study uses a qualitative approach with a descriptive-analytical research type conducted at MI Ma'arif NU Islam Fitriah Lumajang. Data were obtained through non-participant observation, semi-structured interviews, and documentation studies, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results show that Islamic school culture functions as a value system integrated into religious routines, moral habits, teacher role models, and institutional policies. The implementation of Islamic educational values takes place through three main strategies, namely daily worship habits, educator role models, and the integration of Islamic values into learning. Daily religious practices not only shape worship awareness, but also foster religious attitudes, discipline, responsibility, and politeness among students. Thus, Islamic school culture acts as a mechanism for the systematic and continuous internalization of values in strengthening the identity of Islamic education at the Madrasah Ibtidaiyah level.